Contradictory discourses of health promotion and disease prevention in the educational curriculum of Norwegian public health nursing: A critical discourse analysis. Issue 1 (February 2014) - Dahl, Berit Misund; Andrews, Therese; Clancy, Anne
Aims: Health care is under constant change creating new and demanding tasks for public health nurses. The curriculum for public health nursing students is controlled by governmental directives that decide the structure and content of their education. This paper analyses manifest and latent discourses in the curriculum, in order to reveal underlying governmental principles for how public health nurses should promote health and prevent diseases. Methods : A critical discourse analysis of the Norwegian public health nursing curriculum was conducted. Results : The study indicates i) 'a competing biomedical and social-scientific knowledge-discourse', with biomedical knowledge dominating the content of the curriculum; ii) 'a paternalistic meta-discourse', referring to an underlying paternalistic ideology despite a clear focus on user participation; and iii) 'a hegemonic individual discourse'. Even though the curriculum stipulates that public health nurses should work at both an individual and a societal level, there is very little population focus in the text. Conclusions : Recent political documents concerning public health nursing focus more on health promotion, however, this is not sufficiently explicit in the curriculum. The lack of emphasis on social scientific knowledge, and the blurred empowerment and population perspective in the curriculum, can lead to less emphasis on health promotion work in public health nursing education and practice. The curriculum should be revised in order to meet the recent governmental expectations.